Study on outcome of smoking cessation attempt at quit smoking clinic in a health clinic - Zainal Abidin, Muhammad 'Adil; Kadir @Shahar, Hayati; Abd Manaf, Rosliza (Community Health Society Malaysia (CHSM), 2016)
Background: Smoking is the leading preventable cause of non-communicable disease worldwide. Therefore effort for effective measure in smoking cessation will be beneficial. However, relapse is the central problem in the treatment of nicotine addiction. Understanding the relapse phenomena in smoking cessation program will promote better informed intervention and ultimately to achieve lifelong abstinence among the smokers. Due to the paucity of studies regarding the time to smoking relapse in this country, the objective of this study is to determine the time and survival curve of smoking cessation among the smokers attending a quit smoking clinic in one of health clinic at Kuala Lumpur. This study also aims to describe the characteristics of smokers and to determine factors that are associated with smoking cessation and relapse. Methodology: A retrospective cohort study will be conducted using raw secondary data from a quit smoking clinic in a health clinic at Kuala Lumpur. About 770 smokers attending the clinic to participate in the program between 2008 and 2014 using simple random sampling method were identified. Medical records were reviewed to determine their characteristics and their outcome until December 2015. A standard proforma will be used to collect the data from the medical records. Data Analysis: Both descriptive and inferential statistics will be used. Kaplan meier estimate will be used to describe the survival curve of the quit attempt. Multivariate analysis using Cox proportional hazards model to determine significant factors associated with cessation and relapse, and to obtain its hazards ratio. Expected Outcome: The median time of smoker to the first relapse is expected to be different compared to existing local data given the heterogeneity of the sample populations. However, the median time to the successful smoking cessation is expected to be no different since the approach is to set a target quit date a priori compared to flexible quit date approach.